The impact of structural reform strategies of international financial institutions on the rule of law, good governance and development in Pakistan - Ahmed, Naveed (2012)
This thesis examines the impact of structural reform strategies of International Financial Institutions (IFIs) on the rule of law, good governance and development in Pakistan. In doing so, it explores the extent to which the ethos and instruments of rule of law and good governance could be helpful in mitigating problems of social justice as experienced by Pakistan. One important outlet through which this is explored is the internal factors that have aggravated conditions of poverty and social injustice. The interface of these social variables is made possible by the scale of Pakistan’s social challenges which has culminated in the involvement of IFIs in the country’s internal struggles. But like other countries, the IFIs involvement in Pakistan’s domestic affairs has aggravated social injustice rather than alleviating it. The principal argument of this thesis is that absence of social justice in Pakistan could be attributed to the interaction between IFI policies, weak structures of governance and the rule of law. While IFIs policies have recently attempted to emphasise human rights, good governance and the rule of law, these have been ineffective partly because of IFI submissiveness to strategic interests of the United States and Western powers. The theoretical and analytic framework of the thesis is mediated through Amartya Sen’s capability approach. Capability means: What people can positively achieve is influenced by economic opportunities, political liberties, social powers, and the enabling conditions of good health, basic education, and the encouragement and cultivation of initiatives. The institutional arrangements for these opportunities are also influenced by the exercise of people’s freedoms, through the liberty to participate in social choice and in the making of public decisions that impel the progress of these opportunities (Sen, 1999:5). The theoretical framework is used as the frame upon which to engage the impact of Structural Reform Strategies of IFIs on the rule of law, good governance and development in Pakistan as the case study.